Identifying the impact of RelA overexpression in triple-negative breast cancer cells using mass spectroscopy-based proteomics and metabolomics analysis - Zaher, Dana M.; Abdin, Shifaa; Semreen, Mohammad H.; Al-Hroub, Hamza M.; Giddey, Alexander D.; Sharaf, Basma M.; Soares, Nelson C.; Omar, Hany A. (Chemistry & biodiversity, 2025)
RelA protein expression is linked to triple-negative breast cancer (TNBC) aggressiveness and poor prognosis. Consequently, it is crucial to investigate the molecular changes that underlie breast cancer progression and chemotherapy resistance associated with RelA overexpression. In this study, we performed a comprehensive qualitative analysis of proteomics and metabolomics in TNBC cells overexpressing RelA, compared to TNBC cells with basal levels. Trapped ion-mobility spectrometry time-of-flight mass spectrometry was employed to achieve high-resolution analysis. The results unveiled 27 significantly dysregulated proteins in MDA-MB-231 RelA cells relative to MDA-MB-231 cells. The upregulated proteins in MDA-MB-231 RelA cells include interferon-induced protein with tetratricopeptide repeats 3 and cytochrome b5, which are involved in tumor progression and regulation of the cellular redox system, respectively. In addition, metabolomics analysis revealed 21 altered metabolites, such as cyclic AMP and pyridine. The integrated analysis of multi-omics data highlighted the most significantly impacted pathways, including ABC transporters, arginine biosynthesis, and purine metabolism, among others. This study effectively provides valuable insights into potential proteins, metabolites, and signaling pathways that mediate the aggressiveness of TNBC through RelA. Moreover, the multi-omics integrated analysis elucidated the role of RelA in chemotherapy resistance, tumor progression, migration, and invasion, which suggests potential biomarkers and novel therapeutic targets.
Gesehen am 17.11.2025